Influence of evenness of poultry manure application on grain crops productivity - T. Yu. Anisimova; K. K. Kaskin; E. A. Lukashin (Сельскохозяйственные машины и технологии, 2015)
Possibility of increase of efficiency of poultry manure application due to more evenness of fertilizer application into the soil was investigated. Machines with a wide range of regulation of an application rate, for example ROU-6 with interval from 4 to 80 t/ha are for this purpose necessary. Efficiency of poultry manure application for grain crops was increased due to using of machines of drum type with optimum doses fertilizing (12-16 t/ha). An assessment of efficiency was carried out. The drums rotation speed, shovel quantity and shape, their installation angle and a design of the directing board were determined. The developed modified working of a spreader of drum type allowed to reduce unevenness of width fertilizing by 12-14 percent, on length of unit pass - by 5 percent. It was established that if the dose increases more than 8 t/ha, the crop productivity growths not significant. At reduction of fertilizing unevenness from 97 to 72 percent yield losses decrease by 54.4 percent. At reduction of fertilizing unevenness more than 97 percent, efficiency worsens by 58 percent. Poultry manure spreading by the machine and tractor unit MTZ-82.1 + ROU-6M afforded an yield by 38 percent higher, in comparison with the machine and tractor unit T-150K + PRT-10. At decrease in unevenness from 82 to 43 percent of barley loss decreased by 29 percent. It was revealed that spreading by machine ROU-6M provided a yield increase by 8.6 percent more, than by machine PRT-10. Yield losses because of spreading unevenness made: by the PRT-10 operating - 30 percent; by the ROU-6M operating - 0.33 percent. The grain yield increase was higher thanks to more evenness of fertilizer application by ROU-6M with the new spreading working element.